Molecular Basis for CCRL2 Regulation of Leukocyte Migration - Schioppa, Tiziana; Sozio, Francesca; Barbazza, Ilaria; Scutera, Sara; Bosisio, Daniela; Sozzani, Silvano; Del Prete, Annalisa (Frontiers in Cell and Developmental Biology, 2020)
CCRL2 is a seven-transmembrane domain receptor that belongs to the chemokine receptor family. At difference from other members of this family, CCRL2 does not promote chemotaxis and shares structural features with atypical chemokine receptors (ACKRs). However, CCRL2 also differs from ACKRs since it does not bind chemokines and is devoid of scavenging functions. The only commonly recognized CCRL2 ligand is chemerin, a non-chemokine chemotactic protein. CCRL2 is expressed both by leukocytes and non-hematopoietic cells. The genetic ablation of CCRL2 has been instrumental to elucidate the role of this receptor as positive or negative regulator of inflammation. CCRL2 modulates leukocyte migration by two main mechanisms. First, when CCRL2 is expressed by barrier cells, such endothelial and epithelial cells, it acts as a presenting molecule, contributing to the formation of a non-soluble chemotactic gradient for leukocytes expressing CMKLR1, the functional chemerin receptor. This mechanism was shown to be crucial in the induction of NK cell-dependent immune surveillance in lung cancer progression and metastasis. Second, by forming heterocomplexes with other chemokine receptors. For instance, CCRL2/CXCR2 heterodimers were shown to regulate the activation of 2-integrins in mouse neutrophils. This mini-review summarizes the current understanding of CCRL2 biology, based on experimental evidence obtained by the genetic deletion of this receptor in in vivo experimental models. Further studies are required to highlight the complex functional role of CCRL2 in different organs and pathological conditions.